Variation in physiological and work shade levels between cities (Tripoli - Benghazi – Houn) as a model study in applied climate. (Faculty of Education Scientific Journal, 2024)
study aims to determine the months of rest and discomfort, and most efficient months for work and production, in three Libyan cities (Tripoli - Benghazi - Hun). These cities differ in terms of geographical and astronomical location and degree of elevation. Three climatic clues were applied (effective temperature - bioclimatic curve).  - Singer chart), based on monthly climate data for temperature and relative humidity for stations of Tripoli, Benin and Hun for period (1948-2004); To determine the most comfortable and efficient times to work in these cities, as well as developing bioclimatic classification for each city. study concluded that the variation in location of the studied climate stations is related to the variation in the months of rest and work efficiency. The cities of Tripoli and Benghazi, according to the effective temperature, are more comfortable than city of Hon, and are better than them for achieving it.  For three comfortable months during the day according to Singer chart; Due to low levels of relative humidity, then the city of Benghazi recorded two months of rest, while city of Tripoli did not achieve two months of rest due to high relative humidity. three cities differed in the number of most efficient months for working during the day, and they did not achieve any months of rest during the day or night periods.  Houn's climate is comfortable compared to cold, humid climate of Benghazi, and the thermally comfortable, humidly annoying climate of Tripoli
Keywords: climatic comfort; bioclimate; minimum relative humidity; Singer chart; work efficiency